Digestibility and Ruminal Fermentation Characteristic of Native Grass Silage Supplemented with Different Levels of Leucaena leucocephala - Putra, Ryan Aryadin; Noviandi, Cuk Tri; Umami, Nafiatul (Faculty of Animal Science, Universitas Gadjah Mada, ISSTAP 2017, 2017)
This study was conducted to determine the digestibility of native grass silage supplemented with different levels of Leucaena leucocephala. The study was designed using completely randomized design with 3 levels supplementation of Leucaena (10, 20, and 30%) and each treatment was done in 6 replications. All of the silage treatments were inoculated with 4% Lactobacillus plantarum, and stored in mini-silos for 21 days. The results showed that supplementing native grass with 20% Leucaena resulted in the greatest (P<0.05) dry matter and organic matter digestibilities. However, the greatest digestibility of crude protein obtained at 10% Leucaena supplementation and that digestibility decreased linearly with the increasing levels of supplementation (P<0.05). Although there were no effects was detected due to Leucaena supplementation on culture rumen pH and VFA concentration, a significant decrease of NH3-N concentration and significant increase of rumen microbial protein were noticed (P<0.05) as the level of Leucaena supplementation was increased. These data indicate that supplementing native grass with 30% Leucaena is the best treatment in term of microbial protein yield, although nutrient digestibilities were lower than the other treatments.